1999
DOI: 10.1063/1.124985
|View full text |Cite
|
Sign up to set email alerts
|

Phonon-assisted tunneling and interface quality in nanocrystalline Si/amorphous SiO2 superlattices

Abstract: We report on the interface quality and phonon-assisted tunneling in nanocrystalline Si (nc-Si)/amorphous SiO2 (a-SiO2) superlattices (SLs) prepared by magnetron sputtering and thermal crystallization of nanometer-thick a-Si layers. Phonon-assisted tunneling is observed in a bipolar nc-Si based structure, which confirms that the nc-Si/a-SiO2 junction is not only abrupt but also nearly defect free. The conclusion is supported by capacitance–voltage measurements from which the estimated interface defect density i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…11 Thermal crystallization of nanometer thick a-Si layers, however, seems to be a largely uncontrolled step, and it is certainly a complicated one; 12,13 depending on the initial a-Si layer thickness, the shape of Si nanocrystals ͑NCs͒ can be spherical, oval, pyramidal, and even laterally elongated with bricklike Si NCs separated by grain boundaries. 11,14,15 Different experiments show that these grain boundaries are sources of structural defects ͑mainly dangling bonds and residues of amorphous Si͒, and that they are responsible for charge trapping leading to limitations in the device applications of such Si nanostructures. 13 In this letter, we demonstrate that elastically strained Si nanolayers ͑NLs͒ with a low-density of grain boundaries and a lateral-to-vertical aspect ratio close to 100 to 1 can be fabricated using controlled thermal annealing of ultrathin a-Si layers sandwiched between ultrathin SiO 2 films.…”
mentioning
confidence: 99%
“…11 Thermal crystallization of nanometer thick a-Si layers, however, seems to be a largely uncontrolled step, and it is certainly a complicated one; 12,13 depending on the initial a-Si layer thickness, the shape of Si nanocrystals ͑NCs͒ can be spherical, oval, pyramidal, and even laterally elongated with bricklike Si NCs separated by grain boundaries. 11,14,15 Different experiments show that these grain boundaries are sources of structural defects ͑mainly dangling bonds and residues of amorphous Si͒, and that they are responsible for charge trapping leading to limitations in the device applications of such Si nanostructures. 13 In this letter, we demonstrate that elastically strained Si nanolayers ͑NLs͒ with a low-density of grain boundaries and a lateral-to-vertical aspect ratio close to 100 to 1 can be fabricated using controlled thermal annealing of ultrathin a-Si layers sandwiched between ultrathin SiO 2 films.…”
mentioning
confidence: 99%
“…Tunneling superlattice structures comprised of alternating layers of nanocrystalline Si and SiO 2 are also being investigated for the development of quantum superlattice devices. 17 Strain induced by nanofabrication of GeSi quantum dots and superlattices can induce lattice distortions that change the symmetry properties of electronic wave functions in a manner not realized by quantum confinement in itself. 18 Lattice strain can transform the lowest interband transitions to induce direct gap behavior, thereby opening up the possibility of eliminating phonon-mediated recombination.…”
Section: Reduced Dimensional Structuresmentioning
confidence: 99%
“…Several works analyzed the thermodynamic and kinetic of Si thermal crystallization in a-Si/SiO 2 superlattices (Grom et al 2000;Tsybeskov et al 2010Tsybeskov et al , 1999Zacharias and Streitenberger 2000;Zacharias et al 1999). It was clearly demonstrated that the crystallization temperature increases rapidly with decreasing a-Si layer thickness below 10 nm .…”
Section: Introductionmentioning
confidence: 98%